Echocardiographic assessment of COVID19 sequelae in survivors with elevated cardiac biomarkers. (1st August 2022) - Ródenas-Alesina, Eduard; Rodríguez-Palomares, José; Bach-Oller, Montse; Jordán, Pablo; Badia, Clara; Herrador, Lorena; García-de-Acilu, Marina; Clau-Terré, Fernando; González-del-Hoyo, Maribel; Fernández-Galera, Ruben; Servato, Luz; Casas, Guillem; et al.
Abstract: Aims: We sought to determine, using advanced echocardiography, the prevalence and type of cardiovascular sequelae after COVID19 infection with marked elevation of cardiovascular biomarkers (CVB), and their prognostic implications. Methods: All patients admitted from March 1st to May 25th, 2020 to a tertiary referral hospital were included. Those with cardiovascular diseases or dead during admission were excluded. Patients with hs-TnI > 45 ng/L, NT-proBNP>300 pg/mL, and D-dimer >8000 ng/mL were matched with COVID controls (three biomarkers within the normal range) based on intensive care requirements and age, and separately analyzed. Results: From 2025 patients, 80 patients with significantly elevated CVB and 29 controls were finally included. No differences in baseline characteristics were observed among groups, but elevated CVB patients were sicker. Follow-up echocardiograms showed no differences among groups regarding LVEF and only slight differences between groups within the normal range. Hs-TnI patients had lower myocardial work and longitudinal strain. The presence of an abnormal echocardiogram was more frequent in the elevated CVB group compared to controls (23.8 vs 10.3%, P  = 0.123) but mainly associated with mild abnormalities in deformation parameters. Management did not change in any case and no major cardiovascular events except deep vein thrombosis occurred after a median follow-up of 7 months. Conclusion: Minimal abnormalities in cardiac structure and function are observed in COVID19 survivors without previous cardiovascular diseases who presented a significant CVB rise at admission, with no impact on patient management or short-term prognosis. These results do not support a routine screening program after discharge in this population. Graphical abstract: Unlabelled Image Highlights: Previously healthy COVID19 survivors have a low prevalence of echocardiographic abnormalities. Abnormalities are only borderline and mainly in myocardial deformation parameters. Male patients, with hsTnI >45 ng/l or admitted to ICU have more abnormal findings. Abnormalities correlate with excellent prognosis and no change in management. Our data do not support routine echocardiographic screening of COVID19 survivors.